Acute Respiratory Distress Syndrome and Shunt Detection With Bubble Studies: A Systematic Review and Meta-Analysis. (7th November 2022) - Odenbach, Jeffrey; Dhanoa, Sumeet; Sebastianski, Meghan; Milovanovic, Lazar; Robinson, Andrea; Mah, Graham; Rewa, Oleksa G.; Bagshaw, Sean M.; Buchanan, Brian; Lau, Vincent I.
Abstract : OBJECTIVE: Acute respiratory distress syndrome (ARDS) is a life-threatening respiratory injury with multiple physiological sequelae. Shunting of deoxygenated blood through intra- and extrapulmonary shunts may complicate ARDS management. Therefore, we conducted a systematic review to determine the prevalence of sonographically detected shunts, and their association with oxygenation and mortality in patients with ARDS. DATA SOURCES: Medical literature analysis and retrieval system online, Excerpta Medica dataBASE, Cochrane Library, and database of abstracts of reviews of effects databases on March 26, 2021. STUDY SELECTION: Articles relating to respiratory failure and sonographic shunt detection. DATA EXTRACTION: Articles were independently screened and extracted in duplicate. Data pertaining to study demographics and shunt detection were compiled for mortality and oxygenation outcomes. Risk of bias was appraised using the Joanna-Briggs Institute and the Newcastle-Ottawa Scale tools with evidence rating certainty using Grading of Recommendations Assessment, Development and Evaluation methodology. DATA SYNTHESIS: From 4, 617 citations, 10 observational studies met eligibility criteria. Sonographic detection of right-to-left shunt was present in 21.8% of patients (range, 14.4–30.0%) among included studies using transthoracic, transesophageal, and transcranial bubble Doppler ultrasonographies. Shunt prevalence may be associated with increased mortality (risk ratio, 1.22; 95% CI, 1.01–1.49; p = 0.04, very low certainty evidence) with no difference in oxygenation as measured by Pao 2 :Fio 2 ratio (mean difference, –0.7; 95% CI, –18.6 to 17.2; p = 0.94, very low certainty). CONCLUSIONS: Intra- and extrapulmonary shunts are detected frequently in ARDS with ultrasound techniques. Shunts may increase mortality among patients with ARDS, but its association with oxygenation is uncertain.